الفرق الضالة واثرها على عقيدة أهل السنة والجماعة: نموذج من برناوي دار السلام = Islamic Deviationist Movements (IDMs) and Its Impact on Ahl al-Sunnah wa al-Jamaah in Brunei Darussalam - Yousif, Ahmad (International Islamic University Malaysia, 2007)
Frequently, contemporary Muslim thinkers have tended to employ the term “Islamic Deviationist Movements (IDMs) or Ajaran Sesat (in Malay) to denote any group that has strayed from the mainstream of Islam. By way of contrast, Western scholars have often preferred to use the more constructive term “New Religious Movements” (NRMs) to designate any new, “breakaway” religious group from a traditional religion. While Muslim writers have approached the subject from a historical or socio-religious perspective, few have utilized a scientific methodology based on fieldwork experience in order to study Islamic “deviationist” movements; particularly those of mystical orientation. This paper will examine the controversy over defining the term “deviation group.” We briefly compare Western and Islamic methodologies for studying IDMs, and then assess the impact of IDMs on Muslim society. Finally, and in light of the contemporary situation in Southeast Asia, a number of recommendations will be made on how Muslim scholars can effectively study and better understand Islamic “deviation” movements within the purview of a scientific framework.